Simulator evaluation of a prototype device to reduce medication errors in anaesthesia. (8th August 2016) - Khan, S. A.; Khan, S.; Kothandan, H.
Summary: We undertook a randomised control led trial to evaluate the effect of a prototype device which attaches to the intravenous drug administration port, and allows injection of intravenous drugs only after the user scans the barcode on the syringe label. This requires two steps: first, that the correct drug label is generated; and second, that the syringe‐with‐label is scanned before administration. Ten anaesthetists, who were unaware of the primary outcome being measured, administered general anaesthesia for two simulated standardised cases each without and with our prototype (control and intervention, respectively). The primary outcome measured was compliance with a safe drug administration procedure (defined as a two‐step procedure where, step one is scanning a drug ampoule to print a label for a syringe and step two is scanning of the labelled syringe before administering it intravenously). A total of 182 intravenous drug administrations occurred in the study (91 in each group). We found that the use of our prototype increased safe drug administration behaviour in experienced anaesthetists; 33 (36.3% [95% CI 26–47%]) vs. 91 (100% [95% CI 96–100%]) in the control and intervention groups, respectively (p = 0.0001).